DETERMINATION OF COLOR PROPERTIES OF SOME SEEDS - Abeer ABDELSALAM; Tarek FOUDA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this research to determine of color properties of seed related to help in safe passage for seed through cleaning and separation processes. Also investigate some seed properties can be used in design and development of multi-seed planting machine. Soya bean, wheat, corn, cotton faba bean and sunflowers were tested at department of agriculture engineering, faculty of agriculture, Tanta University, Egypt. Through 2022. The design of feed mechanism system required easy movement for seeds this is a critically moving during the filling of the feed disk, so must detriments of the small differences in the surface area and topography of the grains and determine some image analyses. There are clear differences between faba bean and soybean in Hue value was 0. 626. the intensity, and the browning index was 91.75 and 16.25 in faba bean while in soybean were 0. 565,85.33, and 21.79 respectively. While the differences between corn and wheat in Hue value was 0. 699.Also the intensity, and the browning index was 100.08, 17.30 in corn while in wheat were 0. 708. 97.94, and 13.38 respectively. Also, clear differences between cotton and sunflowers in Hue value was 0. 634. Also the intensity, and the Black & White band was 87.40, and 87.40 in cotton while in sunflowers were 0. 480, 96.75 and 96.75 respectively.